Design and analysis of frequency agile LP to CP convertor loaded silicon–graphene based MIMO array antenna in THz regime - Kushwah, Vivek Singh; Reddy, M. Ramana; Charyulu, M. Lakshmi Narasimha; Sastry, P. Narahari; Goyal, Shally (Journal of optics (New Delhi), 2025)
In this communication, a hybrid radiator (graphene-silicon ceramic) in THz frequency regime is designed and discussed. Three main features of proposed antenna are: (a) array-based structure enhance the gain of radiator to 10.0 dBi; (b) a suspension of polarization convertor creates the CP waves in between 6.01–6.45 THz; (c) machine learning (ML) algorithms i.e. random forest and XGboost are utilised to predict the reflection coefficient characteristics of designed antenna, which reduces the effective simulation time for designing of proposed radiator. A reconfigurability in operating band as well as circular polarization band is achieved by coating of graphene over the silicon ceramic and by making graphene-based polarization convertor respectively. HFSS/CST-MWS and with assistance of ML algorithms, it is confirmed that the designed operates in between 5.2–6.55 THz with an isolation level more than 25 dB. Good value of diversity factors and steady far-field features make the antenna design suitable for THz based wireless applications.